Aerogel for Highly Efficient Photocatalytic Degradation - Xue-Chun Yang; Jing-Tai Zhao (Gels, 2024)
Photocatalysis is one of the effective ways to degrade pollutant antibiotics. Agar is used as the adsorption module to provide abundant pore structure. Carbon dots (CDs) are selected as light energy conversion components. Graphitic carbon nitride (g-C3N4) is used as the main material of the catalyst. Agar/CDs/g-C3N4-functionalized aerogel with a unique 3D pore structure is assembled. The Agar/CDs/g-C3N4 aerogel shows the highest photocurrent density, which is 3.7 times that of agar, 2.4 times that of 3-g-C3N4 and 1.6 times that of Agar/g-C3N4 aerogel. Compared with 3-g-C3N4 and Agar/g-C3N4 aerogel, which can completely remove AMX after 75 min, Agar/CDs/g-C3N4 aerogel can degrade amoxicillin (AMX) completely after 45 min of illumination. The reason is that Agar/CDs/g-C3N4 aerogel has a larger specific surface area, richer functional groups, a wider spectral range, higher photocurrent density and better carrier migration and separation efficiency. It is a good strategy with which to combine the effects of each component in the ternary system for the efficient photocatalysis of organic pollutants.